2015
DOI: 10.1038/jhh.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is associated with left ventricular dilatation in primary hypertension

Abstract: Metabolic syndrome (MS) has been shown to predict cardiovascular events in hypertension. Recently, a new four-group left ventricular (LV) hypertrophy classification based on both LV dilatation and concentricity was proposed. This classification has been shown to provide a more accurate prediction of cardiovascular events, suggesting that the presence of LV dilatation may add prognostic information. We investigated the relationship between MS and the new classification of LV geometry in patients with primary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…The effect of MetS on LV geometry is not limited to the development of concentric LVH. Ratto et al have found a three times higher risk of developing LV chamber dilatation in hypertensive patients with MetS even after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The effect of MetS on LV geometry is not limited to the development of concentric LVH. Ratto et al have found a three times higher risk of developing LV chamber dilatation in hypertensive patients with MetS even after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 97%
“…The LV Hypertrophy is an important and independent risk factor for cardiovascular events . So, it is an important therapeutic endpoint in hypertensive patients to prevent and/or to reduce LVH …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is a clustering of cardiovascular risk factors, including insulin resistance, abdominal obesity, dyslipidemia, and hypertension . Intensive studies have established that metabolic syndrome is closely linked to hypertension . Recent studies have found that metabolic syndrome and its components independently predict the risk of NAFLD .…”
Section: Discussionmentioning
confidence: 99%